Design of modern turbine combustors - Mellor, A. M. [ed.] (London Academic Press, 1990)
Lower pollutant emissions and broader multifuel flexibility are driving forces for advancing aircraft, vehicular, and industrial engine performance and versatility. Both are inherently connected with the design of the fuel injector and combustor system. The traditional concerns of improving durability and fuel economy over the life of the engine remain additional requirements.**This volume offers a comprehensive treatment of modern practice aimed both at those in the field and newcomers interested in research and development for gas turbine combustors. Detailed description and assessment of a range of combustor design models and methods; specification and evolution of fuels and fuel injectors; system models for fuel effects on engines and airframes Evaluation of laser-based measurement techniques for combustor flow field studies
Keywords: Turbines -- Design and construction; Turbine design